Community Empowerment through The Hygiene and Competitive Production of Balobo Salted Fish - Erwin Ubwarin; Nelson Gaspesz; Sostones Y. Sisinaru (MITRA: Jurnal Pemberdayaan Masyarakat, 2019)
Maluku Province is the national source of a fishery, the overload production urges society to use the fish salting method because it is unable to absorb by the market. One of the process results is Balobo fish from Aru Island which is tasteful and delicious, but there is no Halal Certification and Food Production Certificate - Household industry made low sales, with traditional production methods that not yet utilize technology furthermore results in low quality and quantity. Because of that, the purpose of community empowerment is to increase the hygiene and competitive production of balobo salted fish. The purpose of these activities is to increase the economy of the society whose acts as the producer of balobo salted fish, and to execute the program of the Ministry of Research, Technology, and Higher Education. The used method is design thinking, socialization, production equipment training, reduce the water content in salted fish to long-lasting, and check the nutrient content. The objectives of the activities are mindset alteration of society from conventional production to technology, hygiene production process, halal certification from Majelis Ulama Indonesia, has the nutrient content information and the enhancement of product endurance by reducing the water content in the product. The conclusion is Maluku has a huge fishery potential, one of which is salted fish, by changing the mindset and technology furthermore it can increase the society's standard of living. The proposal is monetary aid for the capital and complex machinery to accelerate the production and sales process. Keywords: Balobo Fish, Competitive, Hygiene